2010
DOI: 10.1007/s11060-010-0179-8
|View full text |Cite
|
Sign up to set email alerts
|

Stereotactic radiotherapy using Novalis for skull base metastases developing with cranial nerve symptoms

Abstract: Skull base metastases are challenging situations because they often involve critical structures such as cranial nerves. We evaluated the role of stereotactic radiotherapy (SRT) which can give high doses to the tumors sparing normal structures. We treated 11 cases of skull base metastases from other visceral carcinomas. They had neurological symptoms due to cranial nerve involvement including optic nerve (3 patients), oculomotor (3), trigeminal (6), abducens (1), facial (4), acoustic (1), and lower cranial nerv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
37
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(38 citation statements)
references
References 10 publications
1
37
0
Order By: Relevance
“…[10][11][12] In this study, 29 (4%) patients underwent surgery for a SBM during the reviewed period.…”
Section: Discussionmentioning
confidence: 89%
See 1 more Smart Citation
“…[10][11][12] In this study, 29 (4%) patients underwent surgery for a SBM during the reviewed period.…”
Section: Discussionmentioning
confidence: 89%
“…[10][11][12] Patients with SBM are typically only offered radiation therapy in the form of stereotactic radiosurgery, whole-brain radiation, or proton beam therapy. 6,10-13 Surgical interventions are withheld because the surgical outcomes for patients with SBM remain unclear.…”
Section: Introductionmentioning
confidence: 99%
“…Localized radiotherapy or stereotactic radiotherapy is also benefi cial in multiple inoperable cases or in those with skull base metastases. 6,7 Chemotherapy is targeted for the primary tumor and recent Phase I studies have shown some benefi t of Temozolamide alone or in combination with capecitabine is a well-tolerated regimen even in breast metastases. [8][9][10][11] A combination oral VRL plus capecitabine is anotherPhase II trial safe regimen used in cases which have already been treated with chemotherapy.…”
Section: Discussionmentioning
confidence: 99%
“…[12] Postoperative radiotherapy is used to control the residual disease, where there is subtotal removal either to preserve the cranial nerve functions, vital vascular structures, and the brainstem. [13,14] Novalis stereotactic radiotherapy (SRT) has been used in high doses (30-50 Gy in 10-14 fractions) as a safe and effective treatment modality to treat skull base metastases from visceral carcinomas with sparing of normal structures and it was shown that in majority of the patients cranial nerve deficits were improved either completely or partially. [14] Because of the non-availability and non-affordability, fractionated stereotactic radiotherapy (FSRT) or stereotactic radiosurgery (SRS) could not be offered to the patient as noninvasive treatment alternatives to microsurgery either for the primary control of the disease or for control of post-operative pain.…”
Section: Discussionmentioning
confidence: 99%